Reducing the Nitrate Content in Vegetables Through Joint Regulation of Short-Distance Distribution and Long-Distance Transport - Liang, Guihong; Zhang, Zhenhua (Frontiers in Plant Science, 2020)
As an important nitrogen source, nitrate (NO3-) absorbed by plants is carried throughout the plant via short-distance distribution (cytoplasm to vacuole) and long-distance transportation (root to shoot), the two pathways that jointly regulate the content of NO3- in plants. NO3- accumulation within the vacuole depends on the activities of both tonoplast proton pumps and chloride channel (CLC) proteins, and less NO3- is stored in vacuoles when the activities of these proteins are reduced. The ratio of the distribution of NO3- in the cytoplasm and vacuole affects the long-distance transport of NO3-, which is regulated by the proteins NPF7.3 and NPF7.2 that play opposite but complementary roles. NPF7.3 is responsible for loading NO3- from the root cytoplasm into the xylem, whereas NPF7.2 regulates the unloading of NO3- from the xylem, thereby facilitating the long-distance transport of NO3- through the roots to the shoots. Vegetables, valued for their nutrient content, are consumed in large quantities; however, a high content of NO3- can detrimentally affect the quality of these plants. NO3- that is not assimilated and utilized in plant tissues is converted via enzyme-catalyzed reactions to nitrite (NO2-), which is toxic to plants and harmful to human health. In this review, we describe the mechanisms underlying NO3- distribution and transport in plants, a knowledge of which will contribute to breeding leafy vegetables with lower NO3- contents, and thus be of considerable significance from the perspectives of environmental protection and food safety.